Compulsory Psychiatric Treatment of Offenders in Serbia – Legislative Frameworks, Current State and Recommendations - Batrićević, Ana (Zbornik Instituta za kriminološka i sociološka istraživanja, 2014)
Although criminal offences committed by persons in the condition of mental incompetence or substantially diminished mental competence constitute a small percentage of the entire crime rate, mental condition of these perpetrators and the potential danger that they represent for the community require specific state reaction in the form of special medical (curative) security measures of compulsory psychiatric treatment – either in or outside a medical institution. Having in mind the importance of mental health of both – general population as well as the persons who have committed illegal acts prescribed by the law as criminal offences in the state of mental incompetence or substantially diminished mental competence, and the necessity to protect fundamental human rights of the persons who are undergoing psychiatric treatment, the author of this paper analyzes legislative framework for imposing the security measures of compulsory psychiatric confinement and treatment in a medical institution and compulsory psychiatric treatment at liberty, the argumentation pro et contra some legal provisions regulating that field, the role of psychiatric expertise in such cases and current conditions for the application of these measures in the Republic of Serbia. With respect to the goals pointed out in the Strategy for the development of mental health protection, the author highlights certain legislative inaccuracies, practical oversights, and problems in this area and makes some recommendations in order to overcome these issues.